2017
DOI: 10.1002/slct.201702190
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Semiconductor Nanospheres‐Anchored Graphene Oxide Sheets for Effective Microwave Absorption

Abstract: Considerable attention has been given in recent years towards the development of electromagnetic interference (EMI) shielding materials. In spite of the fact that leading polymer composites containing different magnetic and dielectric nanofillers have been used broadly, nevertheless, the impact of inorganic semiconducting nanomaterials has not been utilized fully. Herein, we have designed hollow ZnS nanospheres doped reduced graphene oxide sheets (rGO) via template-free, onepot hydrothermal synthesis process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The measured BET surface area, pore size, and pore volume of the synthesized SPION@T3TIAA-Ag nanocatalyst indicate the enhancement of active sites of surfaces and surface adsorption process. [92] F I G U R E 1 0 Nitrogen adsorption/desorption of SPION@T3TIAA-Ag nanocatalyst 3.9 | Catalytic performance of SPION@T3TIAA-Ag magnetic nanophotocatalys…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The measured BET surface area, pore size, and pore volume of the synthesized SPION@T3TIAA-Ag nanocatalyst indicate the enhancement of active sites of surfaces and surface adsorption process. [92] F I G U R E 1 0 Nitrogen adsorption/desorption of SPION@T3TIAA-Ag nanocatalyst 3.9 | Catalytic performance of SPION@T3TIAA-Ag magnetic nanophotocatalys…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Najim et al 27 prepared Ni–P coated tetrapod-shaped ZnO and showed that a combination of magnetic and dielectric materials exhibits an excellent absorption material (∼−36.41 dB). To combine with dielectric materials and overcome the drawbacks of poor dispersion and agglomeration of nanoparticles, carbonaceous conductive materials such as reduced graphene oxide (rGO) with large specific surface area, 28 excellent thermal, high dielectric dissipation capacity 29 and chemical stability has been introduced. Although higher permittivity on the absorber surface can lead to higher reflection, which is not useful for impedance matching, to overcome this issue, it is important to choose a polymer with a low surface conductivity to make composites with rGO.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric materials with large surface area in the composite are known to help in the improvement of EMI SE via the combined mechanism of reflection, absorption, and multiple reflection. 28,30 When EMW interacts with the polymeric outer layer of a hybrid composite having a low surface conductivity, majority of the radiation penetrates the inner surface of the material due to the negligible quantity of surface reflection. 31 On the other hand, multiple reflections inside a hybrid composite arise when the material contains a variety of interfaces due to the presence of fillers and polymers with different electrical conductivities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, various conductive and magnetic nanomaterials are extensively used in designing microwave shields. , Very recently, different types of hybrid nanomaterials are also showing their effectivity toward microwave shielding. However, extensive use of conductive nanomaterial mainly causes secondary pollution due to the surface reflection, and the magnetic property generally limits their usage in many cases. To this end, semiconductors (MoS 2 , , CuS, ZnS, ZnO ) have been least explored. However, due to the interesting morphological structures of semiconducting chalcogenides, their excellent applicability has earned extra attraction in this field …”
Section: Introductionmentioning
confidence: 99%